Factors associated with diversity, quantity and zoonotic potential of ectoparasites on urban mice and voles - Maaz, Denny (PLoS One, 2018)
Wild rodents are important hosts for tick larvae but co-infestations with other mites and insects are largely neglected. Small rodents were trapped at four study sites in Berlin, Germany, to quantify their ectoparasite diversity. Host-specific, spatial and temporal occurrence of ectoparasites was determined to assess their influence on direct and indirect zoonotic risk due to mice and voles in an urban agglomeration. Rodent-associated arthropods were diverse, including 63 species observed on six host species with an overall prevalence of 99%. The tick Ixodes ricinus was the most prevalent species, found on 56% of the rodents. The trapping location clearly affected the presence of different rodent species and, therefore, the occurrence of particular host-specific parasites. In Berlin, fewer temporary and periodic parasite species as well as non-parasitic species (fleas, chiggers and nidicolous Gamasina) were detected than reported from rural areas. In addition, abundance of parasites with low host-specificity (ticks, fleas and chiggers) apparently decreased with increasing landscape fragmentation associated with a gradient of urbanisation. In contrast, stationary ectoparasites, closely adapted to the rodent host, such as the fur mites Myobiidae and Listrophoridae, were most abundant at the two urban sites. A direct zoonotic risk of infection for people may only be posed by Nosopsyllus fasciatus fleas, which were prevalent even in the city centre. More importantly, peridomestic rodents clearly supported the life cycle of ticks in the city as hosts for their subadult stages. In addition to trapping location, season, host species, body condition and host sex, infestation with fleas, gamasid Laelapidae mites and prostigmatic Myobiidae mites were associated with significantly altered abundance of I. ricinus larvae on mice and voles. Whether this is caused by predation, grooming behaviour or interaction with the host immune system is unclear. The present study constitutes a basis to identify interactions and vector function of rodent-associated arthropods and their potential impact on zoonotic diseases.